Evaluating the economic and regional impact on national transport and infrastructure policies with accessibility variables - Álvarez-Herranz, Agustín; Martínez-Ruiz, María Pilar (Transport, 2012)
This research aims to gauge the economic impact of the measures set out in the Strategic Infrastructure and Transport Plan, 2005–2020, as implemented by the Spanish government, on regional development. Contributing to regional development, this plan extends high capacity road networks and high performance rail networks in Spain between 2005 and 2020. To evaluate the plan, this research relies on an innovative technique based on panel data and accessibility indicators, which can quantify the plan's economic impact on regional development. Findings from the study provide a valuable tool for economic, geographic, and territorial assessments of policies implemented in the field of transport and infrastructure, whilst also pointing to guidelines for the design and development of further proposals and actions.First Published Online: 21 Dec 2012